Perancangan sistem informasi pengajuan dan simulasi perhitungan kredit oleh nasabah berbasis android pada Bank BJB Cabang Soreang Bandung - Nur Kartini, Karin; Halimah, Siti; Ranti, Resmi; Almamalik, Lukmanulhakim (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
A loan or credit is a form of banking service. The rapid development of digital technology has encouraged the banking industry to implement digitalization in its services, including customer credit services to improve the quality of its services. Bank BJB Soreang Branch already has a digital application for credit services for customers. However, this application does not yet have features that makes it easy for customers to apply and simulate credit calculations by themselves. This study aims to design an information system for submitting and simulating credit calculations by customers at Bank BJB Soreang Branch. To develop this information system, UML diagrams are used as the modeling method and the prototype method as the design method. This android-based system was built using Kodular and FireBase software as the database. The results of this study are in the form of an application designs that can be used at Bank BJB Soreang Branch to assist state civil servants and retirees in applying for and conducting credit simulations independently so that the service for the customer credit application process at Bank BJB Soreang Branch is even better.